Selected social factors affecting the prevalence of mental disorders in children and adolescents in the Czech Republic - Němečková, Klaudie; Hricová, Alena (Journal of Nursing, Social Studies and Public Health, 2023)
The mental health of children and adolescents has been under considerable pressure in the last few years, and more children require professional help. Growing stress in families, increasing pressure (primarily affected by the covid-19 pandemic), the unfavourable economic situation, and the war in Ukraine are very stressful for children and young people. Due to insufficient care capacity, it is necessary to help vulnerable children before they need psychiatric help. The aim of this article is to describe selected social factors affecting the prevalence of mental disorders in children and adolescents. We selected several social factors that affect the psychological health of children and adolescents in the Czech Republic, such as covid-19, social networks, the economic crisis, and the war in Ukraine. We based the selection of social factors on content analysis of relevant documents that we obtained using scientific databases and multi-search engines (EBSCO, Scopus). The results collection, analysis, and filtering were conducted between 2020 and 2022.